2016
DOI: 10.4103/0253-7176.185945
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Indian Psychiatrists to PubMed Listed Mental Health Literature During 1995-2013: an Exploratory Study

Abstract: Introduction:Contribution of Indian Psychiatrists as publications in peer-reviewed journals listed with PubMed and their impact has not been studied. The aim of this manuscript is to assess such contribution using a new article level metric measure. The relative citation ratio (RCR) has been used to assess the quality, quantity, and impact of research output of Indian Psychiatrists.Materials and Methods:Publications by Indian psychiatrists in PubMed during 1995–2013 were collected, their RCR and associated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…3 A study examining the contribution of Indian psychiatrists to PubMed-listed mental health literature between 1995 and 2013, published in the Indian Journal of Psychological Medicine (IJPM), similarly noted that Indian psychiatry's contribution to indexed literature remained modest, and despite a rising number of indexed publications, Indian psychiatric journals continued to have low citation indices. 4 A previous study by one of the authors (CA) of this paper showed that articles published in the IJP under-referenced previously published relevant papers in the same journal 5 ; four years later, there was little change. 6 Based upon this, it was hypothesized that articles published in the IJPM would, similarly, demonstrate a continued trend by Indian researchers A bulletin from the Centre for Scientific and Industrial Research in 2014 described an exponential increase in the publication of research in India, which is now one of the top 10 countries in the world in terms of the number of research papers published.…”
Section: Original Articlementioning
confidence: 67%
See 1 more Smart Citation
“…3 A study examining the contribution of Indian psychiatrists to PubMed-listed mental health literature between 1995 and 2013, published in the Indian Journal of Psychological Medicine (IJPM), similarly noted that Indian psychiatry's contribution to indexed literature remained modest, and despite a rising number of indexed publications, Indian psychiatric journals continued to have low citation indices. 4 A previous study by one of the authors (CA) of this paper showed that articles published in the IJP under-referenced previously published relevant papers in the same journal 5 ; four years later, there was little change. 6 Based upon this, it was hypothesized that articles published in the IJPM would, similarly, demonstrate a continued trend by Indian researchers A bulletin from the Centre for Scientific and Industrial Research in 2014 described an exponential increase in the publication of research in India, which is now one of the top 10 countries in the world in terms of the number of research papers published.…”
Section: Original Articlementioning
confidence: 67%
“…3 A study examining the contribution of Indian psychiatrists to PubMed-listed mental health literature between 1995 and 2013, published in the Indian Journal of Psychological Medicine (IJPM), similarly noted that Indian psychiatry’s contribution to indexed literature remained modest, and despite a rising number of indexed publications, Indian psychiatric journals continued to have low citation indices. 4…”
mentioning
confidence: 99%
“…Changes in Indian MISUDs research mindset and publication focus re-orientation, as advocated earlier is the need of the hour. 26,27 The present study could suffer from biases emanating from poor data representativeness index. 13 Though the DisMod II MR system has inbuilt mechanism to counteract this, the effectiveness of which is unknown.…”
Section: Nonementioning
confidence: 95%
“…The result of the present study can be better read in conjunction, with another study. 14 The study observed the Relative Citation Ratio (RCR), an article level metric promoted by National Institute of Health, USA reveals the citation pattern of Indian Psychiatrists who have published in PubMed related database.…”
Section: 65mentioning
confidence: 99%